FORMULATION AND EVALUATION OF INVASOMAL GEL OF ADAPALENE FOR EFFECTIVE ACNE TREATMENT - MANU SINGHAI,; MOHAN L KORI, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The goal of the present study is to develop and evaluate an invasomal gel of adapalene (ADP) for the effective treatment of acne. Methods: ADP loaded invasomal gel was prepared with required modifications after optimizing formulation variables on the basis of physicochemical properties and % drug entrapment. The data obtained from in vitro drug release study was plotted in various kinetic models following in vivo antiacne activity of ADP invasomal gel and observing the zone of inhibition, index of inflammatory strength, and acne power. Results: The drug content of ADP loaded invasomal gel was lucrative, as the value did not stray from 99.45%. The maximum percentage of drug content was found to be in formulation AIG4, 99.45±0.25%. ADP -loaded invasomal gel had profitable drug content because the value stayed within the range of 99.45%. Formulation AIG4 had the highest proportion of medication content, 99.45±0.25%. The optimized invasomal formulation (AIG4) was shown to match well with Korsmeyers-Peppas model kinetics, which characterizes drug release as a time-dependent diffusion process, useful in the development of efficient transdermal drug delivery systems for ADP, which could lead to a more successful and patient-friendly treatment for acne and other skin conditions. Conclusion: With a high capacity for skin penetration and effectiveness in treating acne, our results suggest that ADP -loaded invasome gel is a promising lipid-based nanosystem for topical ADP administration.